The Influence of Changes in Effective Interest Rates, The Rupiah Exchange Rate And Bank Profitability On Movements in Stock Returns of BUMN Bank ListedON THE INDONESIAN STOCK EXCHANGE FOR THE 2015-2019 PERIOD - Yayan Cahyana,; Aam Abdul Salam,; Abdul Fidayan,; Erna Garnia,; Fahmi Damarjati Ruseka, (Adpebi Science Series, 2023)
The purpose of this research is to determine the United States Effective Interest Rate, Rupiah Exchange Rate and Bank Profitability with the ratio dimensions This research is a cause-and-effect comparison, the data source used is the US central bank, the rupiah exchange rate against the US dollar and the annual reports of state-owned banks from 2015 to 2019 from the Indonesian Stock Exchange. The number of samples is 4 banks in state-owned banking. To analyze the model and test the research hypothesis, we used several statistical methods of panel data regression analysis. the research results and hypothesis tests The American Effective Interest Rate and the Rupiah Exchange Rate simultaneously influence stock returns, and ROA, ROE, and NIM ratios are proven not to affect stock returns.